Seinfeld, The Simpsons, and Seductive Vampire Slayers: A Literature Review of Adult Education and Popular Culture - Robin Redmon Wright; Jennifer A. Sandlin (Adult Education Research Conference, 2008)
This paper summarizes a review of the adult education literature that focuses on popular culture. Six ways that scholars have engaged with popular culture emerged. The authors offer suggestions for future research.
Keywords: popular culture; informal adult learning; public pedagogy; literature review